2017
DOI: 10.1038/ijo.2017.252
|View full text |Cite
|
Sign up to set email alerts
|

The association between BMI and health-related quality of life in the US population: sex, age and ethnicity matters

Abstract: The results show that a more differentiated use of BMI cutoffs in scientific discussions and daily practice is indicated. The findings should be considered in the design of future weight loss and weight management programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 28 publications
(46 reference statements)
2
43
0
Order By: Relevance
“…The inverse U-shape relation between the weight status measured by BMI and the quality of life was found in the US population (Laxy et al 2017). A similar pattern was observed in the Norwegian population aged 40-49, with changes in BMI measured by self-reported questionnaire and health-related quality of life measured by SF-36 (Hervik Thorbjørnsen et al 2014).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The inverse U-shape relation between the weight status measured by BMI and the quality of life was found in the US population (Laxy et al 2017). A similar pattern was observed in the Norwegian population aged 40-49, with changes in BMI measured by self-reported questionnaire and health-related quality of life measured by SF-36 (Hervik Thorbjørnsen et al 2014).…”
Section: Discussionmentioning
confidence: 58%
“…Studies aimed to assess the nature of relationship between obesity and mortality showed an increased risk of death in higher and lower body mass index (BMI) categories, indicating an inverse U-or J-shape relation. On the other hand, there are some studies indicating that overweight can be neutral or even protective against mortality (Aune et al 2016;Bombak 2014;Orpana et al 2010;Laxy et al 2017;Cohen-Mansfield and Perach 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, in contrast to our hypothesis, BMI and education were not signi cantly associated with QoL in black women in univariate models, although those relationships were observed in white women. Previous studies have shown signi cant relationships between BMI, education, and QoL in blacks [9], [10]. However, BMI has shown to be an unreliable parameter for obesity and understanding its relationship on QoL [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that middle-aged black women are biologically older (by about 7.5 years) than white women of the same chronological age due to black women's greater exposure to stressors which can negatively impact QoL [8]. Furthermore, in black women, body mass index (BMI) has been shown to have a negative linear relationship with health-related QoL, compared to the inverse-U shape for white women [9]. Black women have consistently higher BMI levels through all levels of education, whereas white women appear to have decreased BMI with increasing education levels.…”
Section: Introductionmentioning
confidence: 99%